Surface‐enhanced Raman scattering based sensing of trans‐urocanic acid, an epidermal photoreceptor using silver nanoparticles aided by density functional theoretical calculations. (19th March 2019) - Kumar, Naveen; Thomas, Susy; Rao, Rekha; Maiti, Nandita; Kshirsagar, Rohidas Jagannath.
Abstract: Trans‐urocanic acid (t‐UCA) is found predominantly in the stratum corneum of the human skin (4–34 nM/cm 2 ) and acts as photo‐protectant against ultraviolet‐induced DNA damage. On exposure to ultraviolet radiation, t‐UCA isomerizes to cis‐UCA, and recent studies revealed that the immunosuppressive properties of cis‐UCA are linked to skin cancer. Surface‐enhanced Raman scattering (SERS), a surface sensitive technique, enabled the detection of t‐UCA down to 50 picomolar concentration with good signal‐to‐noise ratio. Density functional theoretical calculations were also carried out for a detailed understanding of the Raman vibrations and interpreting the metal–molecule interaction. The orientation of the molecule on the silver surface was also deduced from the observed SERS features along with the density functional theoretical calculations. At 50 μM t‐UCA concentration, the molecule interacts chemically through the carboxylate and π electrons of the ethylenic groups assuming a slightly tilted orientation on the silver surface. At concentrations lower than 50 μM, the molecule assumes a flat geometry on the silver surface enabling the interaction through the carboxylate group, the π electrons of the ethylenic CC bond, and also the imidazole ring. The analytical enhancement factors were calculated for the ethylenic CC and carboxylate stretches and were found to be ~10 8 . This is the first report on the trace level sensing of t‐UCA using SERS that may be of relevance in the dermatological studies. Abstract : The surface‐enhanced Raman scattering technique enabled the detection of trans‐urocanic acid (t‐UCA) down to 50 picomolar concentration with good signal‐to‐noise ratio. The SERS intensities aided by DFT calculations infer that at concentrations lower than 50 μM, the molecule assumes a flat geometry on the Ag surface whereas at higher concentrations, t‐UCA is oriented in a slightly tilted configuration. This study can be extended to elucidate the presence of t‐UCA in the epidermal layer as well as in cosmetic products.